2021
DOI: 10.3390/microorganisms9010133
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent Klebsiella pneumoniae of Lineage ST66-K2 Caused Tonsillopharyngitis in a German Patient

Abstract: Hypervirulent Klebsiella pneumoniae (hvKp) is a novel pathotype that has been rarely described in Europe. This study characterizes a hvKp isolate that caused a community-acquired infection. The hypermucoviscous Klebsiella pneumoniae (K. pneumoniae) strain 18-0005 was obtained from a German patient with tonsillopharyngitis in 2017. Antibiotic susceptibility testing was performed and the genome was sequenced by Illumina and Nanopore technology. Whole genome data were analyzed by conducting core genome multilocus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…This result is consistent with those of our previous study in the ICU ( Zeng et al., 2021 ). Several studies have observed that hvKP over time has been susceptible to antibiotics and related mainly to community-acquired infections ( Klaper et al., 2021 ). However, there are reports where this has been reversed and hvKP with antibiotic resistance and involved in infections associated with hospital care are gradually beginning to appear ( Gu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with those of our previous study in the ICU ( Zeng et al., 2021 ). Several studies have observed that hvKP over time has been susceptible to antibiotics and related mainly to community-acquired infections ( Klaper et al., 2021 ). However, there are reports where this has been reversed and hvKP with antibiotic resistance and involved in infections associated with hospital care are gradually beginning to appear ( Gu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neither ST23-K1 isolate is part of a previously described and globally distributed CG23-I clade and, as such, neither contained the combination of yersiniabactin and colibactin biosynthetics genes observed in ICEKp10 (Fig S6) (18). KPN49 is part of a rarely described ST66-K2 lineage consistent with the recent global re-emergence of this clone (Fig S6) (56,59,60).…”
Section: Phylogenetic Analysis Of Bloodstream Isolates Containing Hvkp Pathogenicity Locimentioning
confidence: 55%
“…The Qubit dsDNA HS Assay Kit (Invitrogen) was used for DNA quantification. DNeasy extracted DNA was sequenced on a NextSeq2000 benchtop device (Illumina) as described before [ 14 ]. The short-read whole-genome sequencing data analysis workflow was performed as described before, including several steps for quality control [ 14 ].…”
Section: Methodsmentioning
confidence: 99%